Retroreflection-based sandwich type affinity sensing of isothermal gene amplification products for foodborne pathogen detection - Lee, Danbi; Kim, Eunsuk; Lee, Kyung Won; Kim, Ka Ram; Chun, Hyeong Jin; Yoon, Hyunjin; Yoon, Hyun C. (Analyst, 2022)
Loop-mediated isothermal amplification (LAMP) is an outstanding method for molecular diagnostics, as the rapid, specific, and sensitive amplification of target genes is possible. However, it is necessary to measure fluorescence in the quantitative analysis of LAMP products, so a sophisticated optical setup is required. This study tried to develop a novel sensing method that can quantify target analytes with simple equipment, such as nonspectroscopic white light and a CMOS camera. To achieve this, a retroreflective Janus particle (RJP) as a probe and specially designed loop primers, fluorescein isothiocyanate (FITC)- and biotin-modified loop primers, were introduced into the LAMP system. By performing LAMP in the presence of designed primers, double-stranded amplicons possessing FITC and biotin labels at each end are generated in proportion to the quantity of the target pathogen. Using the anti-FITC antibody-modified sensing surface and streptavidin-conjugated RJP probes, the amplicons can be captured in sandwich-configuration and detected under nonspectroscopic conditions composed of white light and a camera. To confirm the feasibility of the sensing system, the invA gene of Salmonella was selected as the target. It was possible to quantitatively analyze the Salmonella concentration from 0 to 106 colony-forming units, sufficiently covering the required detection range. In addition, quantitative analyses of pathogens in contaminated food sources, including milk and chicken meat, were successfully conducted with a limit of detection of 10 CFU. This journal is
Keywords: Amplicons; Amplification products; Fluorescein isothiocyanate; Gene amplification; Janus particles; Loop mediated isothermal amplifications; Loop-mediated isothermal amplifications; Retro reflection; Sandwich types; White light; Animals; DNA Primers; Gene Amplification; Milk; Nucleic Acid Amplification Techniques; Salmonella; Sensitivity and Specificity